The Division Ring Over Conjugate Product - Ai-Guo Wu; Hui-Zhen Wang; Yu Teng (IEEE Access, 2019)
In this paper, we investigate the rational fractions in the framework of conjugate product and establish a division ring. Some conjugate properties on the proposed division ring are obtained, and the similarity and consimilarity properties are investigated.